2013
DOI: 10.1021/ef400400n
|View full text |Cite
|
Sign up to set email alerts
|

Application of Novel and Advanced Fuel Characterization Tools for the Combustion Related Characterization of Different Wood/Kaolin and Straw/Kaolin Mixtures

Abstract: The increased demand for energy from biomass enforces the utilization of new biomass fuels (e.g., energy crops, short-rotation coppices, as well as wastes and residues from agriculture and the food industry). Compared to conventional wood fuels, these new biomass fuels usually show considerably higher ash contents and lower ash sintering temperatures, which leads to increased problems concerning slagging, ash deposit formation, and particulate matter emissions. One possibility to combat these problematic behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…However, the smelting phases detected in the present study by means of DTA analysis, together with the SO 2 release detected by TGA-MS evidence the presence of K 2 SO 4 (l) in the samples. In a subsequent study [52], the SALT_F solution was eliminated from the thermodynamic equilibrium calculations in cases where the K/(Si+P) molar ratio in the raw biomass was higher than 1. In that way, it was intended to avoid an overestimation in the precipitation of K salts (carbonates and sulfates), which in turn would yield an unrealistic decay in the AMCs.…”
Section: Ash Melting Curvesmentioning
confidence: 99%
“…However, the smelting phases detected in the present study by means of DTA analysis, together with the SO 2 release detected by TGA-MS evidence the presence of K 2 SO 4 (l) in the samples. In a subsequent study [52], the SALT_F solution was eliminated from the thermodynamic equilibrium calculations in cases where the K/(Si+P) molar ratio in the raw biomass was higher than 1. In that way, it was intended to avoid an overestimation in the precipitation of K salts (carbonates and sulfates), which in turn would yield an unrealistic decay in the AMCs.…”
Section: Ash Melting Curvesmentioning
confidence: 99%
“…Sewage sludge (SS), limestone (LM) and lignosulfonate (LG) were added to reed canary grass (R) in a percentage of 3 wt% (blends R-SS, R-LM and R-LG, respectively). A review of the literature [10,11,20,22,[24][25][26][27]29,30] showed that additives are generally blended with biomass in proportions up to 10 wt%. However, satisfactory results were especially obtained by adding 1-5 wt% of additives.…”
Section: Biomass Fuels Additives and Blendsmentioning
confidence: 99%
“…Additionally, fuel indexes on a molar basis, based on works by Sommersacher et al [27,41] and describing the effect of given elements on alkali release, corrosion risk and ash sintering temperature, were calculated. They correspond respectively to Si/(K + Na), 2S/Cl and (Si + P + K + Na)/(Ca + Mg + Al).…”
Section: R W R-w R-ss R-lm R-lgmentioning
confidence: 99%
See 2 more Smart Citations